2022
DOI: 10.3390/biomedicines10123140
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase C677T Gene Variant in Relation to Body Mass Index and Folate Concentration in a Polish Population

Abstract: Background: Methylenetetrahydrofolate reductase (MTHFR) is an enzyme responsible for producing an active form of folate. The MTHFR T677T genotype may have adverse health effects associated with weight gain and a reduction in folate availability. Aim: In this study, we examined the influence of the MTHFR C677T variant on BMI and determined its role as a risk factor for obesity. We also assessed the relationships between the MTHFR C677T genotype and folate and vitamin B12 concentrations in subjects before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Our results, showing that 5-MTHF and folic acid concentrations were lower in heterozygotes and in homozygotes with methylation disorders caused by MTHFR c.665C>T and c.1286A>C polymorphisms, were consistent with outcomes regarding folic acid provided by other researchers [34,35]. However, in a whole-genome sequencing study it appeared that the other gene located on the same chromosome as MTHFR was responsible for folic acid concentration [36].…”
Section: Discussionsupporting
confidence: 91%
“…Our results, showing that 5-MTHF and folic acid concentrations were lower in heterozygotes and in homozygotes with methylation disorders caused by MTHFR c.665C>T and c.1286A>C polymorphisms, were consistent with outcomes regarding folic acid provided by other researchers [34,35]. However, in a whole-genome sequencing study it appeared that the other gene located on the same chromosome as MTHFR was responsible for folic acid concentration [36].…”
Section: Discussionsupporting
confidence: 91%
“…Lower 5-MTHF and folic acid levels were observed in patients with the c.665C>T homozygous genotype. Our results were not statistically significant, however they are consistent with the 2022 study conducted on the population of 1712 obese people, where it was found that in the case of MTHFR gene polymorphisms (in homozygotes c.665C>T) the concentration of folic acid was significantly lower than in heterozygotes and in the wild type [33]. Our results are consistent with the results of the 2022 study conducted on 1855 postmenopausal women, where lower folic acid concentration and higher homocysteine concentration were found in the homozygous c.665C>T variant of the MTHFR gene [34].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, no statistically significant differences were found in the prevalence of the MTHFR C677T polymorphism between obese and non-obese individuals in 1712 individuals of Polish origin [ 104 ], in a young population in Mexico [ 105 ], or in a population of Brazilian patients [ 106 ]. Regarding the first of the mentioned studies, a correlation was established between excessive body weight, the TT genotype of the MTHFR gene, and reduced folate levels.…”
Section: The Association Of Variants Of the Mthfr ...mentioning
confidence: 99%